Edukasi Tentang Kesehatan Gigi dan Mulut pada Siswa TK Filadelfia Karangan, Kabupaten Tana Toraja - Hayuti Windha; Betriani Disik; Fera Dwiyanti; Suharnita Wijaya (CV. Armas Suan Sejahtera, 2025)
Oral and dental health is part of a person's overall health and is one of the most important factors that needs to be considered for normal growth, especially in children. As children grow older, they begin to consume various types of foods, including sweet foods such as fruit juice, candy, and chocolate. Such sweet foods can damage children's dental health and can cause cavities, black, porous teeth, and bad breath. Therefore, the habit of brushing teeth is a healthy habit that children need to develop to maintain their dental and oral hygiene. The lack of dental hygiene education for children by parents is the main cause of poor dental care from an early age. The purpose of this activity is to educate preschoolers about the importance of dental and oral health, and to get children used to brushing their teeth from an early age. This activity took place at Filadelfia Kindergarten, Karangan, Tana Toraja on October 20, 2025. The implementation of the dental care practice program for children included a lecture, question and answer session, and proper tooth brushing practice. The success of this activity was evident in the participation of all students of Filadelfia Kindergarten, Karangan, Tana Toraja Regency, in the children's dental care practice program.